Formation of organotypic testicular organoids in microwell culture†. Issue 6 (30th March 2019) - Sakib, Sadman; Uchida, Aya; Valenzuela-Leon, Paula; Yu, Yang; Valli-Pulaski, Hanna; Orwig, Kyle; Ungrin, Mark; Dobrinski, Ina
Abstract: Three-dimensional (3D) organoids can serve as an in vitro platform to study cell–cell interactions, tissue development, and toxicology. Development of organoids with tissue architecture similar to testis in vivo has remained a challenge. Here, we present a microwell aggregation approach to establish multicellular 3D testicular organoids from pig, mouse, macaque, and human. The organoids consist of germ cells, Sertoli cells, Leydig cells, and peritubular myoid cells forming a distinct seminiferous epithelium and interstitial compartment separated by a basement membrane. Sertoli cells in the organoids express tight junction proteins claudin 11 and occludin. Germ cells in organoids showed an attenuated response to retinoic acid compared to germ cells in 2D culture indicating that the tissue architecture of the organoid modulates response to retinoic acid similar to in vivo. Germ cells maintaining physiological cell–cell interactions in organoids also had lower levels of autophagy indicating lower levels of cellular stress. When organoids were treated with mono(2-ethylhexyl) phthalate (MEHP), levels of germ cell autophagy increased in a dose-dependent manner, indicating the utility of the organoids for toxicity screening. Ablation of primary cilia on testicular somatic cells inhibited the formation of organoids demonstrating an application to screen for factors affecting testicular morphogenesis. Organoids can be generated from cryopreserved testis cells and preserved by vitrification. Taken together, the testicular organoid system recapitulates the 3D organization of the mammalian testis and provides an in vitro platform for studying germ cell function, testicular development, and drug toxicity in a cellular context representative of the testis in vivo. Abstract : Prepubertal testicular cells undergo in vitro morphogenesis and give rise to spherical organoids with testes-specific tissue architecture.